THE USES OF GOOGLE MAPS IN DIGITAL MARKETING FOR SMALL AND MEDIUM ENTERPRISES (SMEs) IN SUKAMAJU VILLAGE, PESISIR BARAT DISTRICT, LAMPUNG - Dendi, Dendi; Septiani, Tami; Putri, Intan; Syukerti, Nanda; laras, Henny dewi; Suryanti, Poppy (Universitas Sang Bumi Ruwa Jurai, 2024)
In this research, the writer uses a qualitative descriptive approach. In descriptive qualitative research, interpreting and explaining the data obtained by researchers from interviews, observations, documentation, so as to get answers to problems in detail and clearly. This research activity was carried out at the location of Suka Maju Village, Ngaras District, Pesisir Barat Regency, Lampung. This study proves that Small, and Medium Enterprises (SMEs) in Suka Maju Village, Ngaras District, Pesisir Barat Regency, Lampung Province still choose traditional communication, this is due to the slow knowledge of SMEs actors towards online marketing or digital marketing, in using google maps there are still many SMEs actors who do not understand a google maps application, even though this google maps application can help producers and consumers so that the efforts made by producers are known and consumers can easily find information about the efforts that have been made. Lack of knowledge about the use of google maps is also caused by inadequate internet network access factors and the lack of socialization carried out by the community for SMEs in Sukamaju Village.